Use of Electronic Code Book (Ecb) Algorithm in File Security - Philipus Tarigan Tarigan (Jurnal Info Sains : Informatika dan Sains, 2020)
Electronic communication such as sms, e-mail, chat, web, e-banking is a commonly used communication tool today. To prevent the misuse of such data by other parties, a good data security system is required. Cryptography is a way of securing data that aims to maintain the confidentiality of the information contained in the data, so that the data information can not be known by unauthorized parties. In maintaining the confidentiality of information, cryptography encodes plaintext data into an unrecognizable form of password data (chipertext), and although others later obtain the data, it cannot understand its contentsElectronic communication such as sms, e-mail, chat, web, e-banking is a commonly used communication tool today. To prevent the misuse of such data by other parties, a good data security system is required. Cryptography is a way of securing data that aims to maintain the confidentiality of the information contained in the data, so that the data information can not be known by unauthorized parties. In maintaining the confidentiality of information, cryptography encodes plaintext data into an unrecognizable form of password data (chipertext), and although others later obtain the data, it cannot understand its contents